The selection of Sufficiently Efficient ISO LNG Tanks for Applications in Industrial Estates based on Edward Lisowski and Wojciech Czyzycki - Fathan Mubina Dewadi; Raja Aziz Raja Ma’arof (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2022)
Liquefied Natural Gas (LNG) is more likely to employ gasoline in street transportation applications because of its greater cryogenic energy density as a result, the key problem with this technology is the tank mounted on board with the control system and vaporizer board required to give the internal combustion engine (ICE) input. The research approach employed in this study was quantitative research using experimental methodologies because this study necessitates controlling and manipulating one or more independent variables while observing the dependent variable to detect differences based on the independent variables. With a method like this, of course, a tank that is quite efficient can be selected. In terms of profit, it is apparent that it could produce a greater volume of gas than gas to liquid (GTL), because the project of LNG lifespan was more extensive than GTL's. LNG is thus more comercial than GTL.